45.3k views
4 votes
Select the correct answer. What is the simplest form of this expression? (2x − 3)(3x2 + 2x − 1) A. 6x3 − 5x2 − 8x + 3 B. 6x3 − 5x2 − 6x + 2 C. 6x3 − 9x2 − 4x + 3 D. 6x3 − 2x2 − 8x + 3

User Xochitl
by
5.7k points

2 Answers

5 votes

Answer:

Explanation:

So the 2 expressions are being multiplied:

(2x -3)((3x^2 +2x-1) =

(2x)3x2) = 6x^3

(2x)(2X) = 4X^2

(2X)(-1)=-2X

(-3)(3X^2) =-9X^2

(-3)(2X)=-6X

(-3)(-1)= 3

Now add all of the products together to get the final answer =

6x^3-5x^2-8x+3

User Ganbin
by
6.0k points
3 votes

Answer: A. 6x3 − 5x2 − 8x + 3

Step-by-step explanation: this is a multiplication (2x − 3) = A (3x2 + 2x − 1) = B, so we are going to multiply each value from A with every value of B

for example you can start 2X from A

2X . 3X2 = 6X3

2X . 2X = 4X2

2X . -1 = -2X

now with -3

-3 . 3X2 = -9X2

-3 . 2X = -6X

-3 . 1 = -3

mow we can put every value in one equation

6X3 + 4X2 + 2X - 9X2 -6 X - 3

after that, you can simplify the common values for example

4X2 - 9X2 = -5x2

- 2X - 6 X = -8x

this the last equation that we get after simplify

6x3 − 5x2 − 8x + 3

User Akku
by
5.4k points